PENERAPAN PERILAKU HIDUP BERSIH UNTUK MENINGKATKAN KUALITAS HIDUP SEHAT MASYARAKAT DALAM TATANAN KELUARGA - Satria Yuda Perdana Putra; Nandang Rukanda; Dinno Mulyono (IKIP Siliwangi, 2026)
Clean and Healthy Living Behavior (PHBS) refers to all behaviors carried out with awareness so that family members can take care of themselves in terms of health and actively participate in health activities in the community. This study aims to identify and analyze (1) Community habituation to healthy living behaviors. (2) Efforts to implement clean living behavior without cigarette smoke to improve the quality of healthy life of the community within family settings. (3) Effective strategies for implementing clean living behavior without cigarette smoke to improve the quality of healthy life of the community within family settings. (4) Constraints faced in implementing clean living behavior without cigarette smoke to improve the quality of healthy life of the community within family settings. The research method used to address the research questions in this study is qualitative research.